A modular model-driven engineering approach to reduce efforts in software development teams (2014)
Model-driven development (MDD) raises as one of the promising paradigms to solve classical software development problems like bad estimation, low productivity and bad quality. The main goal of this work is to create a Model-driven software development tool called MoDev to reduce efforts in the process of developing applications. This tool focuses mainly on significant improvements in terms of productivity and quality, allowing developers to model applications and generate a meaningful portion of code. MoDev requires predefined software architectures as input and it does not only serves to improve some issues related to software development, but it was also implemented to be easily extended and reusable. Aimed to achieve that, the tool is created following a proper methodology for this approach. By means of a case study, the promises of the MDD were confirmed elucidating important improvements in terms of productivity, quality, maintainability and flexibility. However, some minor issues related to cultural challenges, the need of people with expertise in language engineering and training times were detected as well.